Physics of Spin in Solids: Materials, Methods and Applications
DOI: 10.1007/1-4020-2708-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculations Near Ferromagnetic Quantum Critical Points

Abstract: We discuss the application of the density functional theory in the local density approximation (LDA) near a ferromagnetic quantum critical point. The LDA fails to describe the critical fluctuations in this regime. This provides a fingerprint of a materials near ferromagnetic quantum critical points: overestimation of the tendency to magnetism in the local density approximation. This is in contrast to the typical, but not universal, tendency of the LDA to underestimate the tendency to magnetism in strongly Hubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In FeBS, the same effect is present due to the nonmagnetic interband scattering [118]. Since the Hebel-Slichter peak is not present in this scenario even in a clean sample, see Equation (30), the pair-breaking effect is more subtle: it changes exponential behavior below T c to a more power-law like one. If the impurity-induced bound state lies at the Fermi level (Section 3.4), the relaxation rate acquires a low-temperature linear-T Korringa-like term over a range of temperatures corresponding to the impurity bandwidth [261].…”
Section: Thermal Conductivitymentioning
confidence: 95%
See 1 more Smart Citation
“…In FeBS, the same effect is present due to the nonmagnetic interband scattering [118]. Since the Hebel-Slichter peak is not present in this scenario even in a clean sample, see Equation (30), the pair-breaking effect is more subtle: it changes exponential behavior below T c to a more power-law like one. If the impurity-induced bound state lies at the Fermi level (Section 3.4), the relaxation rate acquires a low-temperature linear-T Korringa-like term over a range of temperatures corresponding to the impurity bandwidth [261].…”
Section: Thermal Conductivitymentioning
confidence: 95%
“…The corresponding physics is, therefore, largely missing when DFT is used in a "local" approximation. This belongs to two major classes: (i) on-site Coulomb fluctuations, also called Hubbard correlations, which are included in a very limited way on the level of the Stoner magnetic interaction (reflecting the first Hund's rule), and (ii) quantum critical fluctuations; examples of such are long range ferromagnetic fluctuations in nearly ferromagnetic metals [30]. The hallmark of the former is underestimation of the tendency to magnetism in a DFT calculation, of the latter -overestimation.…”
Section: Limitations Of Dft Calculationsmentioning
confidence: 99%
“…According to Mazin and others, 61 the overestimation of the tendency of metals towards ferromagnetism within the LDA can be used as an indicator of critical fluctuations in a material. However, for this to be an effective indicator, competing states, such as anti-ferromagnetism need to be ruled out in each material.…”
Section: Fixed-spin Moment Calculationsmentioning
confidence: 99%
“…While Ce-3a site is surrounded by six Co-6c (first nearest) and twelve Co-18h (second nearest) neighbors, the Ce-6c site has six first nearest (Co-18h) and only three (Co-3b) second nearest neighbors. Numerous prior studies [37][38][39][40][41] on the weak itinerant magnetic systems have shown that the choice of functional can be very important in predicting the correct magnetic ground state. Hence, first a comparative analysis of LDA and GGA functional for CeCo 3 was performed.…”
Section: A Properties Of Ceco3mentioning
confidence: 99%